Integrative Transcriptome and Proteome Analyses Provide New Insights Into the Interaction Between Live Borrelia burgdorferi and Frontal Cortex Explants of the Rhesus Brain. Issue 5 (21st February 2020) - Ding, Zhe; Sun, Luyun; Bi, Yunfeng; Zhang, Yu; Yue, Peng; Xu, Xin; Cao, Wenjing; Luo, Lisha; Chen, Taigui; Li, Lianbao; Ji, Zhenhua; Jian, Miaomiao; et al.
Abstract: Borrelia burgdorferi ( Bb ), which is neurotropic, can attack the central nervous system (CNS), leading to the development of various neurologic symptoms. The pathogenesis of Lyme neuroborreliosis (LNB) remains poorly understood. Presently, there is a lack of knowledge of the changes in mRNA and proteins in the CNS following early disseminated Lyme disease. Explants from the frontal cortex of 3 rhesus brains were incubated with medium alone or with medium containing live Bb for 6, 12, or 24 hours. Then, we analyzed identified mRNA and proteins in the frontal cortex tissues, allowing for an in-depth view of the transcriptome and proteome for a macroscopic and unbiased understanding of early disseminated Lyme disease in the brain. Through bioinformatics analysis, a complex network of enriched pathways that were mobilized during the progression of Lyme spirochete infection was described. Furthermore, based on the analysis of omics data, translational regulation, glycosaminoglycan/proteoglycan-binding activity in colonization and dissemination to tissues, disease-associated genes, and synaptic function were enriched, which potentially play a role in pathogenesis during the interaction between frontal cortex tissues and spirochetes. These integrated omics results provide unbiased and comprehensive information for the further understanding of the molecular mechanisms of LNB.